Analysis of the indoor horse riding exercise equipment on the young people - Kang, Seung-Rok; Yu, Chang-Ho; Jung, Gu-Young; Moon, Dong-An; Park, Sang-Yong; Kim, Jung-Ja; Kwon, Tea-Kyu (International journal of precision engineering and manufacturing, 2013)
The purpose of this study was to investigate the effect of indoor horse riding exercise equipment on the young people in their twenties. We classified the effects into flexibility, muscle strengthening, and muscular reaction. Subjects performed horse riding exercise using SRider (Neipplus Co. & Chonbuk National Univ, Korea) that we developed. Twenty male and twenty female subjects were included and they had no experience with horse riding as an exercise and no medical history of falling. Exercise was performed for 45 min a day and 3 days a week during 8 weeks in a constant temperature and humidity environment. Once a week, we conducted the bodyeffect measurements. We measured forward trunk flexion and backward trunk extension to verify the improvement of flexibility. We also measured lumbar joint torque using the BIODEX System3 to verify the improvement of muscle strength and reaction. Our results of flexibility showed that values of forward trunk flexion and backward trunk extension after the exercise were higher than those before the exercise. It also presented that the stimulated three-dimensional movement of the horse riding exercise activated joints and muscles not usually used. Besides, the continuous movement of horse riding can reduce muscle tonus and relax stiff muscles. The muscle strengthening and muscular reaction results showed that peak lumbar joint torque after the exercise was higher than that before the exercise. We found that the horse riding exercise using indoor equipment improved flexibility, muscle strength, and muscular reaction. Moreover, we hope that this work will help us understand the exercise characteristic of this equipment.